2023
DOI: 10.2147/jep.s404321
|View full text |Cite
|
Sign up to set email alerts
|

Pomegranate Seeds and Peel Ethanolic Extracts Anticancer Potentials and Related Genetic, Histological, Immunohistochemical, Apoptotic and Oxidative Stress Profiles: In vitro Study

Abstract: Introduction Owing to their great quantity of hydrolyzable anthocyanins and tannins, the peel and seeds of pomegranate are edible and possess potent anti-oxidant and anti-inflammatory characteristics. This work aims to trace the pomegranate seed and peel ethanolic extracts’ anticancer activity against liver cancer cell line, namely HepG2 and related histopathological, immunohistochemical, genetic and oxidative stress profile. Methods In vitro study for both seed and pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Another study reported that a PPE‐treated hepatic cancer cell (HepG2) revealed necrosis and caused cell membranes and intranuclear eosinophilic structures with nuclear membranes to burst. Under the effect of 80% ethanol extract, an upregulation in the expression of pro‐apoptotic gene and downregulation in the expression of anti‐apoptotic gene were substantially expressed (Nasr et al., 2023 ). In a study of Parameswari et al.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that a PPE‐treated hepatic cancer cell (HepG2) revealed necrosis and caused cell membranes and intranuclear eosinophilic structures with nuclear membranes to burst. Under the effect of 80% ethanol extract, an upregulation in the expression of pro‐apoptotic gene and downregulation in the expression of anti‐apoptotic gene were substantially expressed (Nasr et al., 2023 ). In a study of Parameswari et al.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemicals are ingestible components of plants that have cancer-fighting and cancerpreventive properties. 36 Li et al 37 examined the effects of punicalagin and ellagic acids on the cell cycle, apoptosis, reactive oxygen species (ROS), and mitochondrial trans in HepG2 cells (in vitro). The experimental group received final punicalagin and ellagic acid concentrations of 50 and 100 μM.…”
Section: ■ Pharmacological Properties Of Pomegranate Peelmentioning
confidence: 99%
“…Uncontrolled cell division characterizes cancer, a genetic ailment. Phytochemicals are ingestible components of plants that have cancer-fighting and cancer-preventive properties …”
Section: Pharmacological Properties Of Pomegranate Peelmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is a pathological state of the body, which is characterized by a change in redox homeostasis and the prevalence of oxidative and destructive processes [ 12 , 13 , 14 ]. Ionizing radiation is a classical influence leading to the beginning of the formation of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%